The Contributions and Legacy of One of the Greatest Lomonosov Algebraists, Professor Alexander Vasilevich Mikhalev - Vuković, Mirjana; Pantchichkine, Alexei (Sarajevo Journal of Mathematics, 2024)
No abstract available.